Sistem Cerdas Diagnosa Penyakit Kanker Mulut Rahim Dengan Metode Certainty Factor - Zainap Arianti; Agung Perdananto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Health is a very important part of human life because it is one of the factors in supporting all activities of a person's life. But sometimes there are still many who ignore health as a result of arbitrary patterns and lifestyles and this is related to health conditions. Cervical cancer is cancer that occurs in the uterus, an area of the female reproductive organs which is the entrance to the uterus which is located between the uterus (uterus) and the vaginal opening (vagina). Because there are still many people who don't know the symptoms of the disease, an intelligent system diagnoses cervical cancer early with the website-based certainty factor method, it can be recognized by looking at the symptoms by detecting the disease early, preventing cancer. The certainty factor method is a method used to make decisions. To calculate the value of the level of trust (CF), it takes the value of the Meansure of Believe (MB) and the value of the Meansure of Disbelieve (MD). The MB and MD scores were obtained through interviews with doctors and previous research journals. The tools used in this study are the Windows 10 operating system, visual studio code programmer, and the database used as data storage is xampp. The final result of this study resulted in a Web-Based Intelligent System for Diagnosing Cervical Cancer.